PERAN PEKERJA SOSIAL DALAM MENANGANI KORBAN PENYALAHGUNAAN NARKOBA - Supit, Merliani Ivone (Istek Widuri Jakarta, 2017)
Drug abuse problem is increasing in Indonesia, the victim is more and more. One of the efforts undertaken is the intervention process by social workers by using is the role of drivers, the role of liaison, the role of advocacy, the role of the negotiator, the protective role, the role of facilitation, the role of the initiator, the role of the negotiator, the role of the educator and the role of the counselor.